(untitled) (Eurasian Research Bulletin, 2023)
The life and health of every person is the greatest social wealth of society. In this family, the school puts the issue of forming a healthy lifestyle in front of the places dealing with human education and development. Everyone’s health is naturally determined by a healthy lifestyle.